Lysosomes and Cancer Progression: A Malignant Liaison - Machado, Eda R.; Annunziata, Ida; van de Vlekkert, Diantha; Grosveld, Gerard C.; d’Azzo, Alessandra (Frontiers in Cell and Developmental Biology, 2021)
During primary tumorigenesis isolated cancer cells may undergo genetic or epigenetic changes that render them responsive to additional intrinsic or extrinsic cues, so that they enter a transitional state and eventually acquire an aggressive, metastatic phenotype. Among these changes is the alteration of the cell metabolic/catabolic machinery that creates the most permissive conditions for invasion, dissemination, and survival. The lysosomal system has emerged as a crucial player in this malignant transformation, making this system a potential therapeutic target in cancer. By virtue of their ubiquitous distribution in mammalian cells, their multifaced activities that control catabolic and anabolic processes, and their interplay with other organelles and the plasma membrane (PM), lysosomes function as platforms for inter- and intracellular communication. This is due to their capacity to adapt and sense nutrient availability, to spatially segregate specific functions depending on their position, to fuse with other compartments and with the PM, and to engage in membrane contact sites (MCS) with other organelles. Here we review the latest advances in our understanding of the role of the lysosomal system in cancer progression. We focus on how changes in lysosomal nutrient sensing, as well as lysosomal positioning, exocytosis, and fusion perturb the communication between tumor cells themselves and between tumor cells and their microenvironment. Finally, we describe the potential impact of MCS between lysosomes and other organelles in propelling cancer growth and spread.